Analysis of Land Suitability for Avocado Plants (Persea americana M.) in the Educational Forest of the University of Muhammadiyah Mataram - Ahmad Fathoni; Erni Romansyah; Adi Gunawan; Ida Wahyuni; Karyanik Karyanik; I Wayan Sudiyanto (Universitas Muhammadiyah Mataram, 2025)
The 93.55-hectare Mataram Muhammadiyah University Educational Forest has been enriched with eucalyptus and gaharu plants since 2019. In 2024, further enrichment will be carried out with Durian, Avocado, Jackfruit, and Longan plants. The results of previous studies showed that the development plan for Durian plants has a marginal suitability class or S3. This study aims to determine the suitability class and area of land units for Avocado plants as an alternative choice, limiting factors and economic feasibility analysis. Land surveys using the free grid method on 9 land units and land evaluations by matching 14 parameters of land availability and land requirements for Avocado plants, namely soil conditions, climate, and land. The results of the study showed that land suitability for avocado plants was quite suitable (S2) on 3 land units covering an area of 34.15 Ha with limiting factors being texture, soil depth, Total N, Available K and Slope. The land suitability class was marginally suitable (S3) on 6 land units covering an area of 59.4 Ha with limiting factors being slope and soil depth. The investment cost for enrichment of MPTS avocado plants of 100 trees per hectare is Rp. 6,000,000 per hectare and the estimated return on capital is in the 6th year after planting